Applications of triangular glanular flap in hypospadias repairs for different purposes. Issue 1 (February 2014) - Filinte, Gaye Taylan; Akan, Mithat; Temiz, Gökhan; Aycicek Cardak, Gulcin Nujen; Gonullu, Ersin
Abstract Hypospadias is a congenital anomaly of the penis with an ectopic, ventrally-placed meatus due to insufficient development of the anterior urethra. Tubularisation of glanular flaps without plate incision is performed with addition of a triangular flap in order to move the meatus more distally and avoid meatal stenosis. Subcoronally, mid-shaft, and coronally placed 41 hypospadias cases were treated with the tubularisation of the glanular flaps without incision of the urethral plate, a technique similar to TIP technique. Triangular flaps were added at the most distal end of one of the glanular flaps in all cases for different purposes. A medially-based triangular flap was elevated at the distal end of the right-sided longitudinal flap to carry the last suture more distally. The flap increased meatal diameter and carried the last suture more distally. No meatal stenosis was observed for an average of 18.02 (12–30) months. The final localisation of the meatus was satisfactory in all patients. Meatal stenosis, demonstrated after hypospadias repair, is a challenge for both the surgeon and the patient. A distal triangular glanular flap is planned to avoid this challenge. Besides, it helps to carry the meatus more distally. Promising results support the use of the glanular flap while longer follow-up is required for better evaluation.